A internacionalização da capoeira: práticas de apropriação na Argentina, Polônia e Itália - Loureiro, Fábio Luiz (2021)
The researches about the process of internationalization of Capoeira have been mostly focusing on the opinion of those who spread it to the world and not the representations of the practitioners. Taking into consideration the incipient number of investigations centered on the representation of foreign practitioners, the present study aims at overcoming this gap and its main goal is to analyze the appropriation practices of this cultural manifestation operated by the Capoeira players belonging to the so called Beribazu Capoeira Group in Argentina, Poland and Italy. It is a qualitative study with a descriptive-interpretative nature, carried out with 24 participants: six Argentinians, ten Polish and eight Italians. Data was produced through the focal group with 24 participants and the participant observation, with the insertion where the group develops work, experiencing their events and daily activities, such as, baptism, degrees, graduations, capoeira practical courses, speeches, training, lessons and cultural activities. Results indicate that Capoeira has been appropriated in different ways regarding the investigated contexts. Data has also pointed out that, in relation to Capoeira, the Argentinian value, apart from the practice, figures of learning associated with the relational and conceptual dimensions of this cultural manifestation. Although there is an interest in preserving the traditions and the Capoeira rituals, the productive use made by the Argentinian players denotes a copyright appropriation, marked by the sociocultural context in which they are inserted and by personal matters. In Poland, it is observed that there is an ongoing process of appropriation and resignification of this cultural manifestation in the country. At the same time that Capoeira presents singular characteristics, resulting from local traditions and particularities of the ones who use it, cultural aspects found in their motor and symbolic background also impact the way Polish think and act, configuring a movement of cultural circularity. The Polish are proud of the Capoeira built in the last three decades in the country, which creates identity representations among them, articulating aspects of the local culture with the traditions of this Afro-Brazilian manifestation. For the Italians, the meaning of the Capoeira group goes beyond a collective that gathers with the purpose to develop a body practice. It is about a space where the practitioners share love, affection, respect and family life, in the broad sense of the term. They are together, cooperating for the 11 success of the group, committed to the development of the culture they were introduced to and they do not see themselves as foreigners, but Capoeira practitioners. They verbally express their identity and show mastery of the lexicon needed to understand the range of living Capoeira feeling. Regardless the context, it is noticed, in all countries analyzed, an active process of cultural appropriation, in which the aesthetic of reception denotes singular ways to conceive and to related with Capoeira itself, bringing new elements to expand the comprehension of the internationalization processes of such Afro-diasporic manifestation.